ISLAMIC ETHICAL LEADERSHIP: A CONCEPTUAL DISCUSSION - Puteh Salin, Ahmad Saiful Azlin (I-iECONS e-proceedings, 2023)
The purpose of this paper is to explore the leaders’ work ethics from Islamic perspectives towards sustaining the performance of the business organisations. A conceptual discussion based on the character of Prophet Muhammad (pbuh) which sourced mainly from Quran and Sunnah was provided, particularly from the prophetic character namely Siddiq (truthfulness). In addition, this paper also examines and reviews prior studies on directors’ work ethics and ethics from various religious viewpoints. Based on Quran and Sunnah, this paper suggest that the current corporate governance and integrity problems among the directors of the corporate company can be resolved by focusing on the characters and virtues as guided by the Quran and shown by the life of the Prophet Muhammad (pbuh). The outcome of this paper contributes in way of it can be used and applied by the firm and policy makers to construct a comprehensive ethical guideline that based on the prophethood virtues and values.